LEGITIMASI SERTA UPAYA HUKUM ANGGOTA DPR YANG DI PAW OLEH PENGUSUNG PARTAI POLITIK - A.A. KT. Sudiana; Ni Komang Sutrisni (Jurnal Hukum Saraswati (JHS), 2019)
The concept of democracy in a state is explicit as a human right and the constitution House of Representatives members is not a representative of a political party. Supposedly if a member of the House of Representatives is to be dismissed, it must be through the constitutional sovereignty of the people. The Interim Replacement rights of political parties to their members are the rights that can be taken by members of the Parliament to not voice the total votes of the people and there is no freedom of Parliament members to carry out the people's mandate. Based on this, a question can be formulated regarding the legitimacy House of Representatives members in Interim Replacement by Political Party Bearers and the legal remedies House of Representatives members in Interim Replacement by Political Party Bearers. The type of research used is normative legal research and there use a statue approach and analytical concept approach. Legitimacy House of Representatives members in Interim Replacement does not get recognition, guarantees, protection and legal certainty, as well as fair treatment in carrying out their constitutional duties and in fact Interim Replacement right to allow private law (privaatrechtelijk) must override public law. The legal remedies House of Representatives members in Interim Replacement by political party bearers in the form of filing objections to the resolution of internal political party disputes to the Political Party Court, but the regulation contains contradictions, stated that the decision of the Political Party Court is final and binding internally but still opens the possibility of legal efforts to the District Court and Court Great.